1978
DOI: 10.1021/ma60065a038
|View full text |Cite
|
Sign up to set email alerts
|

N-Substituted Poly(α-amino acids). 1. Synthesis and Characterization of Poly(N-methyl-γ-methyl L-glutamate) and Poly(N-methyl-γ-ethyl L-glutamate)

Abstract: N-Substituted Poly(«-amino acids) 1041 stirring at 95 °C until it became homogeneous. This required less than 1 h. Freshly cut sodium metal (0.40 g, 0.018 mol) was then added, and the resulting pink reaction mixture was heated at 95 °C and stirred for 1.5 h. Approximately one-half of the excess phenol was then removed by vacuum distillation. The concentrated reaction mixture was allowed to cool to 40 °C and concentrated HC1 (10 mL) was added, slowly, with stirring. The resulting suspension was poured into 20 v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 4 publications
1
15
0
Order By: Relevance
“…The circular dichroism (CD) spectra of PNMA was also conducted in the aqueous and TFE solution, where the negative Cotton peak at 220–225 nm was observed, indicating formation of a right‐handed helix structure from all‐trans peptide configurations (Supporting Information Fig. S4), that agree with N ‐methylated polypeptides produced by solid‐state synthesis or NCA polymerization in the literature …”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…The circular dichroism (CD) spectra of PNMA was also conducted in the aqueous and TFE solution, where the negative Cotton peak at 220–225 nm was observed, indicating formation of a right‐handed helix structure from all‐trans peptide configurations (Supporting Information Fig. S4), that agree with N ‐methylated polypeptides produced by solid‐state synthesis or NCA polymerization in the literature …”
Section: Resultssupporting
confidence: 76%
“…These polypeptoids have been anticipated to be used as a drug delivery carrier, and construction of antifouling surface . N ‐Substituted polypeptide with substitution group at α‐carbon and amide nitrogen such as poly( N ‐methyl L‐alanine) (PNMA) has an additional feature for the conformation, that is well‐defined secondary structure based on all‐trans peptide configurations . For example, Imanishi et al reported the effect of N ‐substituted polypeptide on the polymerization of NCA as polymer catalysts using these features …”
Section: Introductionmentioning
confidence: 99%
“…Substitution of the nitrogen atom also strongly influences the solubility of oligo‐ and polypeptides . Interestingly, however, the water sorption in polyamides can be decreased by incorporation of N‐methylated polyamide …”
Section: Properties Of Polypeptoidsmentioning
confidence: 99%
“…As an alternative route for the preparation of poly(N-methyl-γ-methyl-L-glutamate) and poly(N-methylγ-ethyl-L-glutamate), they tested different methylation methods on poly(γ-methyl-L-glutamate) or poly(γ-ethyl-L-glutamate). 24 Like poly(N-methyl-L-alanine), both polymers were found to form a right-handed helix in a TFE solution of remarkably high stability, which retained their conformation even in pure TFA as observed by CD (circular dichroism) measurements. 25 A special case is the amino acid proline, the only proteinogenic amino acid containing a secondary amine.…”
Section: Introductionmentioning
confidence: 97%